Slides5

# Slides5 - Course 18.327 and 1.130 Course Wavelets and Filter Banks Modulation and Polyphase Modulation Representations Noble Identities Block

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Course 18.327 and 1.130 Course Wavelets and Filter Banks Modulation and Polyphase Modulation Representations: Noble Identities; Block Toeplitz Matrices and Block z-transforms; and transforms; Polyphase Examples Polyphase Modulation Matrix Matrix form of PR conditions: [F0 (z) F1 (z)] H0(z) H0(-z) = [ 2z –l 0 ] (z)] z) H1(z) H1(-z) 123 Modulation matrix, Hm(z) So So [ F0(z) F1(z)] = [2z –l 0] Hm –1(z) (z)] 0] Hm–1(z) = 1 (z) H1(-z) -H0(-z) z) z) ? -H1(z) H0(z) ? = H0(z) H1(-z) - H0 (-z) H1 (z) (must be non-zero) z) 2 1 2z-l H0(-z) F1(z) = (z) ? 678 678 1 2z-l H1(-z) ⇒ F0(z) = (z) ? Require these Require to be FIR to Suppose we choose ? = 2z - l Suppose 2z Then F1(z) = -H0(-z) (z) 678 678 F0(z) = H1(-z) 3 Synthesis modulation matrix: Complete the second row of matrix PR conditions by replacing z with –z: by F0(z) F1(z) H0(z) z -l H0(-z) 0 =2 123 F0(-z) F1(-z) H1(z) H 1 (-z ) z) 0 (-z) - l z) Synthesis Synthesis modulation modulation matrix, Fm(z) Note the transpose convention in Fm(z). 4 Noble Identities 1. Consider x [n] H(z2) u[n] U(z) = H(z2)X(z) Y(z) = ½ {U(z ½ ) + U( -z ½ )} Y(z) U( )} ↓2 y[n] (downsampling) = ½ { H (z) X (z ½ ) + H(z) X (-z½ )} (z) H(z) )} = H(z) • ½ {X (z ½) + X (-z ½ )} ⇒ can downsample H(z) (z )} can first First Noble identity: First x [n] y[n] x[n] y[n] 2) ≡ H(z) ↓2 H(z ↓2 5 2. Consider 2. Consider x[n] [n] H(z) u[n] U(z) = H(z) X(z) U(z) Y(z) = U(z2) = H(z2) X(z2) ↑2 y[n] (upsampling) ⇒ can upsample first can first Second Noble Identity: x[n] y[n] x[n] [n] ≡ H(z2) ↑2 H(z) ↑2 y[n] 6 Derivation of Polyphase Form 1. Filtering and downsampling: Filtering downsampling x[n] y[n] H(z) ↓2 H(z) = Heven(z2) + z -1 Hodd(z2); heven[n] = h[2n] H(z) ); hodd[n] = h[2n+1] Heven(z2) x[n] + z-1 ↓2 y[n] Hodd(z2) 7 Heven(z2) ↓2 x[n] y[n] + z-1 Hodd(z2) ↓2 x[n] xeven[n] ↓2 Heven(z) + z-1 ↓2 xodd[n-1] Hodd(z) y[n] Polyphase Form 8 2. Upsampling and filtering Upsampling and x[n] ↑2 F(z) y[n] F(z) = Feven(z2) + z-1 Fodd (z2) F(z) x[n] Feven(z2) + ↑2 Fodd(z2) y[n] z-1 9 x[n] ↑2 Feven(z2) + ↑2 x[n] Feven(z) Fodd(z2) yeven[n] z-1 ↑2 + Fodd(z) yodd[n] ↑2 y[n] y[n] z-1 Polyphase Form 10 10 Polyphase Matrix Consider the matrix corresponding to the analysis Consider filter bank in interleaved form. This is a block interleaved form. Toeplitz matrix: matrix: M L L 0 0 0 0 h0[3] h0[2] h1[3] h1[2] 0 0 0 0 h0[1] h0[0] h1[1] h1[0] L L L L L Hb= [0] L h0[3] h0[2] h0[1] h0[0] L h1[3] h1[2] h1[1] h1[0] 4-tap Example 11 11 Taking block z-transform we get: Hp(z) = = = h0[0] h0[1] h1[0] h1[1] [1] + h0[0] + z-1 h0[2] [2] h1[0] + z-1 h1[2] H0,even (z) H1,even (z) z-1 h0[2] h0[3] h1[2] h1[3] h0[1] + z-1 h0[3] h1[1] + z-1 h1[3] H0,odd (z) H1,odd (z) 1,odd (z) This is the polyphase matrix for a 2-channel filter bank. 12 12 Similarly, for the synthesis filter bank: M Fb = M M f0[0] f1[0] f0[1] f1[1] M 0 0 0 0 L f0[2] f1[2] f0[0] f1[0] f0[3] f1[3] f0[1] f1[1] 0 0 0 f0[2] f1[2] 0 f0[3] f1[3] M M L M M 13 13 Fp(z) = = f0[0] f1[0] f0[1] f1[1] + z-1 F0,even [z] F1,even [z] 0,even [z] 1,even [z] F0, odd [z] F1, odd [z] [z] 1, [z] 0, f0[2] f1[2] f0[3] f1[3] Note transpose Note convention for synthesis synthesis polyphase matrix • Perfect reconstruction condition in polyphase domain: Fp(z) Hp(z) = I (centered form) This means that Hp(z) must be invertible for all z on the (z) unit circle, i.e. unit det Hp(eiω) ≠ 0 for all frequencies ω. for 14 14 • Given that the analysis filters are FIR, the Given requirement for the synthesis filters to be also FIR is: FIR det Hp(z) = z-l (simple delay) det because Hp-1(z) must be a polynomial. • Condition for orthogonality: Fp(z) is the transpose Condition (z) of Hp(z), i.e. of HpT(z-1) Hp(z) = I i.e. Hp(z) should be paraunitary. (z) paraunitary 15 15 14243 14243 Relationship between Modulation Relationship and Polyphase Matrices and h0,even[n] = h0[2n] H0(z) = H0,even(z2) + z-1 H0,odd(z2) ; h0,odd[n] = h0[2n+1] H1(z) = H1,even(z2) + z-1 H1,odd(z2) Two more equations by replacing z with -z. Two So in matrix form: H0(z) H0(-z) H 0,even(z2) H0,odd(z2) 1 = H1(z) H1(-z) H 1,even(z2) H1,odd(z2) z-1 123 123 1 -z-1 Hm(z) Hp(z2) Modulation matrix Polyphase matrix 16 16 But 1 1 z-1 -z-1 = 1 z-1 123 11 1 -1 123 D2(z) F2 Delay Matrix 2-point DFT Matrix FN = -1 FN1 = 1 1 1 . . . 1 1 N 1 1…1 w w2 … w N-1 w2 w4 … w 2(N-1) 2π iN ; w=e . . . . . . N-1 w 2(N-1) w (N-1)2 w N-point DFT Matrix FN Complex conjugate: replace w with w = Complex with -i 2π eN 17 17 So, in general 1 Hm(z) F-N = H p(zN) DN(z) N = # of channels in filterbank of filterbank (N = 2 in our example) 18 18 Polyphase Matrix Example: Daubechies 4-tap filter tap 1+√3 3 + √3 1+ h0[0] = h0[1] = 4 √2 4 √2 3 -√ 3 1 - √3 h0[3] = h0[2] = 4 √2 4 √2 1 {(1 + √3 ) + (3 + √3 ) z-1 + (3 - √ 3) z-2 + (1 - √3) z-3} {(1 (3 H0(z) = 4√2 1 {(1 - √3) – (3 - √3) z-1 + (3 + √3)z-2 – (1 + √3)z-3} {(1 3) (3 (3 (1 H1(z) = (z) 4√2 19 19 Time domain: h0[0]2 + h0[1]2 + h0[2]2 + h0[3]2 = h0[0] h0[2] + h0[1] h0[3] = [3] 1 32 + 2√3) + (12 + 6 √3) + 3) (12 – 6 √3) + (4 – 2 √3)} (12 3) =1 {(2√3) + (-2√3)} 1 {(4 {(4 32 =0 i.e. filter is orthogonal to its double shifts 20 20 Polyphase Domain: 1 {(1 + √3) + (3 - √3) z-1} H0,even(z) = {(1 3) 4 √2 = 1 {(3 + √3) + (1 - √3) z-1} {(3 3) 4 √2 H1,even(z) = 1 {(1 - √3) + (3 + √3) z-1} {(1 3) 4 √2 H1,odd(z) 1 { - (3 - √3) – (1 + √3) z-1} (3 3) (1 4 √2 H0,odd(z) 1 Hp(z) = 4√2 = 1 + √3 1 - √3 3 + √3 -(3 - √3) (3 3) 123 A 1 + 4√2 3 - √3 1 - √3 z-1 3 + √3 -(1 + √3) (1 3) 123 B 21 21 Hp(z) = A + B z-1 HpT(z-1) Hp(z) = (AT + BT z)(A + Bz-1) z)(A Bz = (AT A + BTB) + ATBz-1 + BTAz B) AT A 1 1 + √3 1 - √3 1 = (3 4√2 3 + √3 - (3 - √3) 4√2 1 = 32 = 1 + √3 1 - √3 3 + √3 -(3-√3) (4 + 2√3) + (4 - 2√3) (6 + 4√3) - (6 - 4√3) 3) 3) (6 (6 + 4√3) - (6 - 4√3) (12 + 6√3) + (12 - 6√3) 3) (6 3) ¼ √3/4 √3/4 3/4 ¾ 22 22 BT B 1 3 - √3 3 + √3 1 3 - √3 1 - √3 = (1 (1 4 √2 1 - √3 -(1 + √3) 4 √2 3 + √3 - (1 + √3) = = (12 – 6√3) + (12 + 6√3) (6 - 4√3) - (6 + 4√3) (12 3) 3) (4 - 2√3) + (4 + 2√3) (6 3) 3) 32 (6 - 4√3) – (6 + 4√3) 1 ¾ - √3/4 3/4 - √3/4 ¼ ⇒ AT A + BTB = I 23 23 =1 4 √2 1 + √ 3 1 -√ 3 1 3 - √ 3 1 -√ 3 3 + √3 -(3-√3) 4 √2 3 + √3 -(1+√3) 1 = 32 ATB (2 √3) + (-2√3) (-2) – (-2) (2 2) (6) – (6) ( -2 √3) + (2 √3) (6) 3) = BT A = 0 (ATB)T = 0 So HpT(z-1) Hp(z) = I (z) i.e. Hp(z) is a Paraunitary Matrix i.e. (z) Paraunitary 24 24 Modulation domain: 1 H0(z) = P(z) = (-z3 + 9z + 16 + 9z-1 – z-3) 16 1 H0(-z) H0(-z-1) = P(-z) = (z3 – 9z + 16 – 9z-1 + z-3) 9z 16 H0(z-1) So H0(z) H0(z-1) + H 0(-z) H0(-z-1) = 2 i.e. |H0(ω)|^2 + |H0(ω + π)|^2 = 2 25 25 Magnitude Response of Daubechies 4-tap filter. Magnitude response of Daubechies 4-tap filter. 2.5 Frequency response phase 2 1.5 1 0.5 0 -1 -0.8 -0.6 -0.4 -0.2 0 0.2 0.4 Angular frequency (normalized by π) 0.6 0.8 1 26 26 Phase response of Daubechies 4-tap filter. Phase response of Daubechies 4-tap filter. 4 3 Frequency response phase 2 1 0 -1 -2 -3 -4 -1 -0.8 -0.6 -0.4 -0.2 0 0.2 0.4 Angular frequency (normalized by π) 0.6 0.8 1 27 27 ...
View Full Document

## This note was uploaded on 12/04/2011 for the course ESD 18.327 taught by Professor Gilbertstrang during the Spring '03 term at MIT.

Ask a homework question - tutors are online